Kajian Koridor Pelabuhan Kota Tua Ampenan dalam Rangka Menjaga Nilai Sejarah Arsitektur - nada putrie; Rini S. Saptaningtyas; Ismira Bulan Fadhila; Annisa Ayu Nur Saufitri; NS. Shahrastian Rashid (SADE : Jurnal Arsitektur, Planologi dan Teknik Sipil, 2026)
Abstract Urban spatial pattern plays a crucial role in shaping an efficient, organized, and sustainable city structure. The Cakranegara area in Mataram City exemplifies a grid-based spatial layout inherited from traditional HinduBalinese urban planning. This study aims to analyze the morphological characteristics of the Cakranegara area and its implications for urban development. A case study method with a descriptive qualitative approach was employed, including field observation, literature review, and spatial analysis using historical and recent map overlays. The findings reveal that Cakranegara’s grid spatial pattern facilitates mobility, spatial management, and the preservation of cultural and historical values. However, rapid economic growth has pressured open spaces and caused land-use conversions, posing challenges to maintaining the area's sustainability. This study recommends integrating the preservation of urban morphology heritage with adaptive urban development strategies to build a competitive and sustainable city. Kata kunci: urban morphology; spatial pattern; Cakranegara; spatial planning; urban development